(untitled) (Chest & Heart Journal, 2021)
Background: Malignant pleural effusion is a common findings in chest hospital like NIDCH. It may be due to pleural malignancy but mostly due to metastasis. Metastasis mostly occur from bronchial carcinoma but it may occur from any other organs. Sometimes primary site of malignancy is not known. Findings of specific type of malignant cells in pleural effusion or pleural biopsy examination may give information regarding histological type of malignancy. There is no available statistics regarding etiologies and histological type resulting malignant pleural effusion in NIDCH as well as Bangladesh. Aim: To detect the most common type of histological pattern of neoplasm resulting malignant pleural effusion. Which may be an important information for diagnosis and management of malignant pleural effusion. Methods: This was a crass sectional retrospective study, was carried out in the department of respiratory medicine of National Institute of Diseases of Chest and Hospital (NIDCH), Dhaka, during the period of July 2010 to June 2011. Total 69 patients were enrolled consecutively. The information’s regarding malignant pleural effusion was collected from each patient in whom the diagnosis was confirmed by pleural biopsy (done by Abram’s punch biopsy needle) and presence of malignant cells in pleural fluid. Results: Figure II shows that among 69 patients 51(73.91%) patients diagnosed as Adeno-carcinoma and 7(10.15%) patients diagnosed as Squmous cell carcinoma. Lymphoma 4(5.8%) and small cell carcinoma 4 (5.8 %). So malignant pleural effusion is mostly due to adenocarcinoma. Conclusions: So, most common cause of Malignat Pleural effusion is adeno-carcinoma, it may be due to metastasis from bronchial carcinoma or any other part of the body. Chest Heart J. 2020; 44(1) : 28-33